ROBOT MANIPULATOR CONTROL SYSTEMS COMPARISON WITHIN THE CONCEPTS INDUSTRY 5.0 AND INDUSTRY 4.0 (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The article explores the differences in approaches to control systems for manipulator robots within the concepts Industry 4.0 and Industry 5.0. The main requirements for classical control systems focused on automation and autonomy and collaborative systems that take into account interactivity and adaptability for close interaction with a person are analyzed. The comparative analysis highlights the advantages and challenges of each approach, suggesting directions for further developments in the field of adaptive and safe robotics systems.